2016
DOI: 10.12657/steciana.020.011
|View full text |Cite
|
Sign up to set email alerts
|

New occurrence of rare protected moss species Buxbaumia viridis (Bryopsida, Buxbaumiaceae) in the Białowieża Forest

Abstract: The Green Shield-moss Buxbaumia viridis (Bryopsida, Buxbaumiaceae) is an endangered, legally protected bryophyte considered as an ancient forest species both in Poland and elsewhere in Europe. This paper presents new localities for NE Poland, specifically in the Białowieża Forest. As an epixylous species, it is threatened by logging and intensive forest management. It is of utmost importance to protect this species' habitat, particularly at the present time when increased logging is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Until recently, within the Białowieża Forest, only the occurrence of B. aphylla -the species prevalent in lowland Poland -was observed, where it grows on mineral soils in pine forests (Szafran 1957, Atherton et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, within the Białowieża Forest, only the occurrence of B. aphylla -the species prevalent in lowland Poland -was observed, where it grows on mineral soils in pine forests (Szafran 1957, Atherton et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…in contrast, Buxbaumia viridis occurs rarely in Poland, mainly in the carpathians and the Sudety mts., as well as in Poland's lake districts (Szafran 1957;Szmajda et al 1991;Chachuła, Vončina 2010;Hajek 2008Hajek , 2010Hajek , 2012. The species was also reported from the Świętokrzyskie Mts.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of Holá et al [23], Gawryś and Szulc [49], and Deme et al [40] and contradicts the view that only protected areas (nature reserves and national parks such as the BNP) provide suitable habitats for the studied moss species [25] and that strict legal protection is the best way of maintaining B. viridis localities [1]. Thus, calls for creating protective zones around B. viridis localities in managed forests are unsubstantiated [1,10,19,20,31,34,50]. It should be expected that, in addition to the presence of its preferred substrates, the occurrence of B. viridis is determined by factors other than silvicultural procedures, e.g., air humidity [28] and substrate pH or nitrogen/phosphorus proportions [51].…”
Section: Discussionmentioning
confidence: 98%
“…To date, in Poland, B. viridis has been mostly reported to occur on spruce and fir deadwood, less often on beech deadwood [1,5], and only occasionally on humus or mineral soil [8,9]. In 2016, B. viridis was reported for the first time on oak deadwood in the Białowieża Forest, with 78 sporophytes growing on two logs [10]. The current study confirmed that the most suitable substrate for B. viridis is A. alba (its presence was a prerequisite for the selection of survey areas).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation